2005
DOI: 10.2460/javma.2005.227.1782
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic percutaneous ultrasound-guided cholecystocentesis in three dogs with extrahepatic biliary obstruction and pancreatitis

Abstract: Three dogs were examined because of acute pancreatitis. In all 3, distension of the gallbladder was seen ultrasonographically, and extrahepatic biliary tract obstruction (EHBO) was diagnosed on the basis of ultrasonographic findings and serum biochemical abnormalities (i.e., high serum bilirubin and cholesterol concentrations and increased hepatic enzyme activities). In all 3 dogs, percutaneous ultrasound-guided cholecystocentesis (PUCC) was used to decompress the gallbladder, with cholecystocentesis performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…[14][15][16][17][18][19] In human patients, similar risks and complications of traditional open surgeries in debilitated patients have led to the use of interventional radiology-guided procedures (eg, placement of cholecystostomy tubes and percutaneous biliary stenting) and interventional endoscopy techniques (eg, ERCP and biliary stenting) in an effort to minimize procedure-related complications. 22 The use of cholecystostomy tubes 23 or decompressive cholecystocentesis 24 are other minimally invasive options for temporary biliary decompression, although these procedures do not allow drainage of bile salts into the gastrointestinal tract. 22 The use of cholecystostomy tubes 23 or decompressive cholecystocentesis 24 are other minimally invasive options for temporary biliary decompression, although these procedures do not allow drainage of bile salts into the gastrointestinal tract.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19] In human patients, similar risks and complications of traditional open surgeries in debilitated patients have led to the use of interventional radiology-guided procedures (eg, placement of cholecystostomy tubes and percutaneous biliary stenting) and interventional endoscopy techniques (eg, ERCP and biliary stenting) in an effort to minimize procedure-related complications. 22 The use of cholecystostomy tubes 23 or decompressive cholecystocentesis 24 are other minimally invasive options for temporary biliary decompression, although these procedures do not allow drainage of bile salts into the gastrointestinal tract. 22 The use of cholecystostomy tubes 23 or decompressive cholecystocentesis 24 are other minimally invasive options for temporary biliary decompression, although these procedures do not allow drainage of bile salts into the gastrointestinal tract.…”
mentioning
confidence: 99%
“…22 The use of cholecystostomy tubes 23 or decompressive cholecystocentesis 24 are other minimally invasive options for temporary biliary decompression, although these procedures do not allow drainage of bile salts into the gastrointestinal tract. [23][24][25] In 1974, Falkenstein et al 27 reported performing ERCP in healthy dogs for physician training and research purposes and indicated that success in achieving CBD cannulation improved with experience. 25,26 This typically requires enteric bile salt replacement of the drained bile via a feeding tube until patency is reestablished.…”
mentioning
confidence: 99%
“…10,98 Two large retrospective case series have been published reporting on prognostic factors and outcome in biliary diversion surgeries in cats. 36,37 In one, the mortality rate within 48 hours of surgery was 57%; in cats diagnosed with neoplasia it was 100% versus those with non-neoplastic causes, where it was 40%.…”
Section: Biliary Decompression Proceduresmentioning
confidence: 99%
“…The gallbladder can be drained intermittently using needle aspiration under ultrasound guidance (Herman et al 2005). This technique has been described in three clinical dogs without inducing a bile peritonitis.…”
Section: Temporary Bile Diversionmentioning
confidence: 99%